Comparison of fully non linear and weakly nonlinear potential flow solvers for the study of wave energy converters undergoing large amplitude of motions - Letournel, Lucas; Harris, Jeffrey C.; Ferrant, Pierre; Babarit, Aurélien; Ducrozet, Guillaume; Benoit, Michel; Dombre, Emmanuel (Volume 9B: Ocean Renewable Energy, 2014)
International audience We present a comparison between two distinct numerical codes dedicated to the study of wave energy converters. Both are developed by the authors, using a boundary element method with linear triangular elements. One model applies fully nonlin-ear boundary conditions in a numerical wavetank environnment (and thus referred later as NWT), whereas the second relies on a weak-scatterer approach in open-domain and can be considered a weakly nonlinear potential code (referred later as WSC). For the purposes of comparison, we limit our study to the forces on a heaving submerged sphere. Additional results for more realistic problem geometries will be presented at the conference. INTRODUCTION Among the marine renewable energy sources, wave energy is a promising option. Despite the great number of technologies that have been proposed, currently no wave energy converter (WEC) has proven its superiority over others and become a technological solution. Usual numerical tools for modeling and designing WECs are based on boundary elements methods in linear potential theory [1-4]. However WECs efficiency relies on large amplitude motions [5], with a design of their resonance frequencies in the wave excitation. Linear potential theory is thus inadequate to study the behavior of WEC in such configuration.